Comparison of Tactile Temporal Numerosity Judgments Between Unimanual and Bimanual Presentations. (January 2016) - Iida, Naoki; Kuroki, Scinob; Watanabe, Junji
In recent years a growing interest has emerged in numerosity perception in touch. Most of the studies on tactile numerosity perception have investigated its spatial aspect by testing the ability to count the number of items presented simultaneously. On the other hand, only a small number of studies have examined its temporal aspect, and the underlying mechanisms of tactile temporal numerosity judgments (TTNJs) remain elusive. In this study, we presented a rapid sequence of vibrations, each of which was presented to one of two bodily locations, and then compared the performance of the TTNJ between two stimulus-location conditions. In one condition, each of the vibration trains was presented to one of two fingers of the left hand (unimanual condition). In the other condition, each of the vibration trains was presented to the index finger of either the right or left hand (bimanual condition). With these conditions, we aimed to examine how the differences in stimulus locations and in types of tasks affect TTNJ performance. Our results showed that when the participants were asked to count the total number of vibrations presented at two locations, the performance (proportion of correct answers) was not so much different between the two conditions. In contrast, when the participants had to report the two numbers of vibrations presented at each location or to focus on the number of vibrations at a single location, the TTNJ performance in the bimanual condition was drastically better than in the unimanual condition. These results suggest that the underlying mechanism for tactile temporal numerosity perception can segregate the interhemispheric information (bimanual condition) more precisely than the within-hemispheric information (unimanual condition), when spatiotemporal tasks are performed.